Development of climate smart agriculture based on empowering farmers around forests through triple-helix collaboration - Jumiyati, Sri (Interaction, Community Engagement, and Social Environment, 2024)
Background: The agricultural sector policy in Indonesia in facing climate change is to increase agricultural productivity and reduce GHG emissions through the development of Climate Smart Agriculture based on empowering farmers around forests. Methods: Qualitative methods produced descriptive data in the form of written or spoken words from people, and observable behaviour. Findings: Synergy and collaboration between the Government, Universities and the Community in the form of triple-helix collaboration through Climate Smart Agriculture activities, which are carried out through the following activity stages: 1) Technology Transfer Stage, including activities for making corn planting demonstration plots under coconut stands, making planting demonstration plots taro under cocoa stands, creation of Moringa plantation management demonstration plots on dry land; 2) Training Stage, activities are carried out to process agricultural products into secondary products, namely: Corn Flour, Corn Analog Rice, Taro Flour, Taro Analog Rice, Moringa Leaf Powder, and Moringa Leaf Tea; 3) Packaging and e-marketplace initiation stage, through packaging design, labeling, marketing via digital platforms and assistance; 4) Empowerment activities and strengthening the institutional capacity of agricultural extension workers and farmer groups are urgently needed to support the development of climate-smart agriculture. Conclusion: Innovations to support the development of Climate Smart Agriculture based on empowerment around forests through triple-helix collaboration will improve farming management through activities. Novelty/Originality of this Study: The research presents a novel triple-helix collaboration model for developing Climate Smart Agriculture, integrating government, university, and community efforts to enhance agricultural productivity while mitigating greenhouse gas emissions.